2006
DOI: 10.1021/jp063321r
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Activity of Palladium Clusters:  Sorption of Hydrogen

Abstract: Samples of Pd/SiO2 with average cluster size of palladium (d(Pd)) ranging from 1 to 10 nm were prepared by different methods, such as incipient wetness impregnation (IW), ion exchange (IE), and sol-gel (SG). The dispersion (D(Pd)) for prepared Pd/SiO2 samples varied with the method of preparation and showed a trend of IW < IE < SG. Chemical interaction between the dispersed nanopalladium and hydrogen gas was calorimetrically studied as a function of hydrogen uptake. Measured profiles of interaction energy vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 29 publications
(34 reference statements)
4
42
0
1
Order By: Relevance
“…Both the experiment and theoretical calculations showed that hydrogenation of alkenes would occur smoothly on both Pd(111) and Pd(100) [30]. In addition, it has also been reported that ΔE 2H decreased with the size decrease of Pd nanoparticles [31][32][33]. In order to calculate the dissociation adsorption energy of H 2 on different Pd clusters, here, we constructed a set of Pd n with size varying from Pd 2 to Pd 147 .…”
Section: Resultsmentioning
confidence: 99%
“…Both the experiment and theoretical calculations showed that hydrogenation of alkenes would occur smoothly on both Pd(111) and Pd(100) [30]. In addition, it has also been reported that ΔE 2H decreased with the size decrease of Pd nanoparticles [31][32][33]. In order to calculate the dissociation adsorption energy of H 2 on different Pd clusters, here, we constructed a set of Pd n with size varying from Pd 2 to Pd 147 .…”
Section: Resultsmentioning
confidence: 99%
“…The sorption extent and rate depend on the metal cluster size and metal oxidation state. [62][63][64][65][66][67] For these reasons the H L 2 /Pd initial value is an important parameter that affects the sorption phenomena.…”
Section: H Lmentioning
confidence: 99%
“…Accordingly, a new experimental system has been developed to investigate the proton irradiation of mass-selected protonated water clusters. Many different techniques have been used successfully to generate ensembles of water cluster ions including electrospray ionization 6,7 , electron impact ionization 8 , corona discharge ionization 8 , chemical ionization 9 and electrospray droplet impact 10,11 . The novelty of the present experimental system lies in the acceleration (up to 10 kV) and massselection of molecular and cluster ions of water prior to 0.9-2.5 a.u.…”
Section: Introductionmentioning
confidence: 99%